El nacimiento y ascenso de los civil lawyers - García Long, Sergio (2018)
Civil law has changed. Now, Civil Law has become a European law. Interestingly this European Civil Law has developed in English language.We also must add to the picture the process of globalization of American law. The contract law that is being used by practitioners in corporate and financing deals is based on American contract clauses which are not regulated by civil codes. Many of these deals are written in English language. This new environment of the Civil Law in the international field demands adaption for lawyers if they want to survive in the legal practice.